2020
DOI: 10.1177/0886260519898429
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Disclosure of Sexual Assault: The Potential Impact of Victimization History and Rape Myth Acceptance

Abstract: Victims of sexual assault often disclose their victimization experiences to friends and family members in the hope of gaining support. However, a number of factors may influence the manner in which these confidants respond to the disclosure (e.g., severity of the victim’s assault). The purpose of this study was to examine the role of two unique factors—the disclosure recipient’s sexual victimization history and endorsement of rape myths—in predicting responses to disclosure. Participants were 114 unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The findings also correspond with results obtained by Bottoms et al (71) who found that mock jurors with personal experience of childhood trauma and abuse, were more conviction prone than jurors without such experience. Though not all research adheres to such a conclusion with several studies failing to evidence any such association between personal victimization and juror voting preferences (68)(69)(70)83). An important consideration within the current study was the low frequency of participants who reported such previous sexual victimization experiences, and thus a larger cross-section of sexual abuse survivors may yield different findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings also correspond with results obtained by Bottoms et al (71) who found that mock jurors with personal experience of childhood trauma and abuse, were more conviction prone than jurors without such experience. Though not all research adheres to such a conclusion with several studies failing to evidence any such association between personal victimization and juror voting preferences (68)(69)(70)83). An important consideration within the current study was the low frequency of participants who reported such previous sexual victimization experiences, and thus a larger cross-section of sexual abuse survivors may yield different findings.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to date few empirical studies have explored the link between juror experience of sexual violence and verdict decisions made at trial. Whilst experiences of sexual abuse seem likely to influence juror judgments and verdict selections whilst serving as a rape trial juror, most existing studies found little evidence to support such an association (35,(68)(69)(70). That said, in one recent study, Bottoms et al (71) sought to investigate the importance of jurors' own abuse experiences on subsequent verdict selections when serving as jurors in a child sexual abuse trial.…”
Section: Sexual Victimization and Juror Decisionsmentioning
confidence: 99%
“…These internalized norms, taboos, and stereotypes of sexual violence may express themselves through feelings of shame and self-blame (Kennedy & Prock, 2018) or the minimization and/or trouble labeling the incident as sexual violence (e.g., Mennicke et al, 2021; Wilson & Newins, 2022), and therefore may withhold victims from seeking help. Moreover, these norms, taboos, and stereotypes of sexual violence may affect victims through negative responses or victim-blaming from their social surroundings (Grandgenett et al, 2020; Rich et al, 2021). Although more attention has been paid to victim-blaming in light of various movements (e.g., #MeToo), rape myths may still be present.…”
Section: Discussionmentioning
confidence: 99%
“…Research on rape myth acceptance consistently shows that those who believe common rape myths, such as assuming women lie about being assaulted (for attention from others, for revenge on the accused, etc.) or misconstrue what happened and incorrectly label their experiences as sexual assault, are less likely to respond supportively to disclosures of sexual assault (Edwards et al, 2011; Grandgenett et al, 2020; Lonsway & Fitzgerald, 1994; Rich et al, 2021; Suarez & Gadalla, 2010; Wilson et al, 2021). Likewise, research on the stigma of mental illness highlights that people assume those with mental health problems are confused, unreliable, and untruthful (Corrigan & Bink, 2005).…”
Section: Discussionmentioning
confidence: 99%